Penggunaan Media Video Pembelajaran Akidah Akhlak dalam Pembentukan Karakter Peserta Didik Kelas V MIS YAPIT Bontobiraeng Kabupaten Gowa - Rasyid, M.; Naro, Wahyuddin; rosdiana (Primer Edukasi Journal, 2024)
This research aims to: (1) Presenting How to Use the Ahlak Akidah Learning Video Media in Class V MIS YAPIT Bontobiraeng, Gowa Regency. (2) Knowing How to Learn the Akhlak Aqidah in Class V MIS YAPIT Bontobiraeng, Gowa Regency. (3) Knowing whether the use of video media in learning the moral creed can shape the character of Class V students at MIS YAPIT Bontobiraeng, Gowa Regency. The type of research used is a type of qualitative research using a phenomenological approach. Methods of data collection is done by observation, interviews, and documentation. The results in this study indicate that the use of video media for teaching moral principles in class V MIS YAPIT Bontobiraeng is divided into two stages, namely the preparation stage and the implementation stage. Aqidah Akhlak learning in class V MIS YAPIT Bontobiraeng in presenting learning is still based on the syllabus and lesson plans. The use of aqidah moral learning video media can shape the character of students in class V MIS YAPIT Bontobiraeng, it is clear that positive changes in student character, after using learning video media, students who are lazy or are often late, become diligent and are never late again due to the learning process. Its presentation is easy and fun to make students interested and excited in the learning process.